2022
DOI: 10.5551/jat.63019
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Serum Lipoprotein(a) Levels to Lipoprotein and Apolipoprotein Profiles and Atherosclerotic Diseases in Japanese Patients with Heterozygous Familial Hypercholesterolemia: Familial Hypercholesterolemia Expert Forum (FAME) Study

Abstract: The official journal of the Japan Atherosclerosis Society and the Asian Pacific Society of Atherosclerosis and Vascular Diseases Original Article Aims: Lipoprotein(a) [Lp(a)] is a plasma lipoprotein consisting of a low-density lipoprotein (LDL)-like particle with apolipoprotein (Apo)(a), attached via a disulfide bond to Apo B100. Previous studies have shown that high Lp(a) levels are associated with an increased risk of cardiovascular disease in patients with familial hypercholesterolemia (FH). To date, limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Our results are in line with these results. Recently, lower mean Lp(a) levels were found in a Japanese cohort (20.8 mg/dl; 208 mg/L) ( Naito et al, 2021 ) and in a previous other Japanese study (21.9 mg/dl; 219 mg/L) ( Tada et al, 2018 ), demonstrating the importance of racial differences. Significantly increased Lp(a) levels in females were previously described in FH ( Alonso et al, 2008 ), as well as in patients with CVD ( Virani et al, 2012 ) and PAD ( Forbang et al, 2016 ), and in the general population ( Banerjee et al, 2011 ).…”
Section: Discussionmentioning
confidence: 81%
“…Our results are in line with these results. Recently, lower mean Lp(a) levels were found in a Japanese cohort (20.8 mg/dl; 208 mg/L) ( Naito et al, 2021 ) and in a previous other Japanese study (21.9 mg/dl; 219 mg/L) ( Tada et al, 2018 ), demonstrating the importance of racial differences. Significantly increased Lp(a) levels in females were previously described in FH ( Alonso et al, 2008 ), as well as in patients with CVD ( Virani et al, 2012 ) and PAD ( Forbang et al, 2016 ), and in the general population ( Banerjee et al, 2011 ).…”
Section: Discussionmentioning
confidence: 81%
“…When there is an innately elevated serum Lp(a) level, the association between Lp(a) and CVD events among patients with FH produces controversial results [ [28] , [29] ]. Several studies among general populations have suggested that Lp(a) and CRP appear to have synergistic effects in the development of CVD events [ [11] , [12] ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to their rarity, the accumulation of the data of these intractable diseases is not adequate for their natural history, current clinical situations, and factors associated with prognosis. However, several large scale registry studies have clarified some useful clinical information and genetic backgrounds [23][24][25][26][27][28][29] . Therefore, it is essential to understand the unique profiles of these diseases in Japan for frequency, phenotype, and genotype and their clinical prognosis, hopefully, based on the registration of all the patients, to help useful feedback to the current guidelines for their diagnosis and management.…”
Section: Study Participantsmentioning
confidence: 99%